Infection frequency of Epstein-Barr virus in subgingival samples from patients with different periodontal status and its correlation with clinical parameters - Wu, Yan-min (Zhejiang University Press, 2006)

(untitled)
Objective: To detect the infection frequencies of different genotypes of Epstein-Barr virus (EBV) in subgingival samples from chronic periodontitis (CP) patients, and to discuss the correlation between infection with EBV and clinical parameters. Methods: Nested-PCR assay was used to detect EBV-1 and EBV-2 in subgingival samples from 65 CP patients, 65 gingivitis patients and 24 periodontally healthy individuals. The amplicons were further identified by restriction fragment length polymorphism analysis (RFLP) with endonucleases Afa I and Stu I. Clinical parameters mainly included bleeding on probing (BOP), probing depth (PD), attachment loss (AL) in six sites of the dentition. Results: In CP patients, gingivitis and periodontally healthy individuals, the infection frequencies were 47.7%, 24.6% and 16.7% for EBV-1, and 15.4%, 7.7% and 0% for EBV-2, respectively. In 2 out of the 65 CP patients co-infection of EBV-1 and EBV-2 was found. The positive rate of EBV-1 in chronic periodontitis patients was higher than that in gingivitis patients (P=0.01) and periodontally healthy individuals (P=0.01). But no significant difference was shown in EBV-1 frequency between gingivitis patients and healthy individuals (P>0.05) or in EBV-2 frequency among the three groups (P>0.05). In CP patients, higher mean BOP value was found in EBV-1 or EBV-2 positive patients than that in EBV negative ones (P<0.01), but with no statistical difference in the mean PD or AL value between EBV positive and negative patients (P>0.05). After initial periodontal treatment, 12 out of the 21 EBV-1 positive CP patients did not show detectable EBV-1 in subgingival samples. Conclusion: nPCR plus RFLP analysis is a sensitive, specific and stable method to detect EBV-1 and EBV-2 in subgingival samples. Subgingival infection with EBV-1 is closely associated with chronic periodontitis. Infection of EBV in subgingival samples was correlated with BOP.